Environmental Performance, Working Capital Efficiency, and Bankruptcy Risk: Evidence from Indonesian Listed Firms - Ihsan Ro'is; Benjamin Chadwick; Tz-Li Wang (Yayasan Ghalih Pelopor Pendidikan, 2026)
Corporate bankruptcy remains a major concern in Indonesia, where firms face challenges not only from financial fragility but also from regulatory compliance and operational inefficiencies. Traditional bankruptcy prediction models largely emphasise financial ratios, overlooking sustainability performance and liquidity management. This study examines the effect of environmental performance, measured by PROPER ratings, and working capital efficiency, measured by the cash conversion cycle, on the bankruptcy risk of non-financial firms listed on the Indonesia Stock Exchange between 2011 and 2023. Panel regression with firm and year fixed effects is employed. Bankruptcy risk is assessed through Altman Z-scores and validated with Ohlson O-scores. The results show that firms with higher PROPER ratings have significantly lower bankruptcy risk, while longer cash conversion cycles increase the probability of distress. The effects remain robust across alternative measures and industry sub-samples. Furthermore, environmental performance moderates the negative impact of inefficient working capital management. This study is among the first to integrate environmental ratings (PROPER) into bankruptcy prediction models in Indonesia and demonstrates that sustainability practices mitigate the risks associated with poor working capital management.